Environmental impacts of coronavirus disease 2019 (COVID-19). (September 2021) - Singh, Veer; Mishra, Vishal
Abstract: The coronavirus disease (COVID-19), a variant of Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2) originated in Wuhan city of China and has now transmitted over the world. Till the April 24, 2020, nearly 144, 367, 284 confirmed positive cases with 3, 066, 270 deaths worldwide. The recent studies have reported that SARS-CoV-2 is transmitted through respiratory droplets. Several vaccines are available now. However, the vaccination process has not completed yet. Worldwide lockdown was initiated to restrict gathering, transport and industrial activities. Lockdown due to COVID-19 showed reduction in environmental pollution. The quality of air and water improved in metro cities and in rivers during COVID-19. This review not only provides the updated information related to impact of COVID-19 on air, water and noise pollution, generation of biomedical waste and global environmental sustainable development but also it covers the basic mechanism of COVID-19 transmission. Graphical abstract: Unlabelled Image Highlights: COVID-19 was first reported in China and transmitted all over the world. Lockdown due to COVID-19 showed positive environmental impacts. Surge in volume of biomedical waste was observed during pandemic. Sustainable technologies play an important role in the environmental protection.